2018
DOI: 10.3171/2018.2.spine171142
|View full text |Cite
|
Sign up to set email alerts
|

Correlation of 2-year SRS-22r and ODI patient-reported outcomes with 5-year patient-reported outcomes after complex spinal fusion: a 5-year single-institution study of 118 patients

Abstract: OBJECTIVEPatient-reported outcomes (PROs) are often measured up to 2 years after surgery; however, prospective collection of longitudinal outcomes for 5 years postoperatively can be challenging due to lack of patient follow-up. The aim of this study was to determine whether PROs collected at 2-year follow-up accurately predict long-term PROs 5 years after complex spinal fusion (≥ 5 levels).METHODSThis was … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2019
2019
2021
2021

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(4 citation statements)
references
References 33 publications
0
4
0
Order By: Relevance
“…To our knowledge, previous studies have not demonstrated a relationship between patient satisfaction and changes in SRS-22R domain scores in ASD patients undergoing a 3CO 1,23,24 . In a multicenter study evaluating 147 consecutive pediatric patient undergoing 3CO Lenke et al reported significant improvements in the SRS-30 Self-Image, function, mental health, and satisfaction domains at a 1-year follow-up 25 .…”
Section: Discussionmentioning
confidence: 85%
See 1 more Smart Citation
“…To our knowledge, previous studies have not demonstrated a relationship between patient satisfaction and changes in SRS-22R domain scores in ASD patients undergoing a 3CO 1,23,24 . In a multicenter study evaluating 147 consecutive pediatric patient undergoing 3CO Lenke et al reported significant improvements in the SRS-30 Self-Image, function, mental health, and satisfaction domains at a 1-year follow-up 25 .…”
Section: Discussionmentioning
confidence: 85%
“…To our knowledge, previous studies have not demonstrated a relationship between patient satisfaction and changes in SRS-22R domain scores in ASD patients undergoing a 3CO. 1,23,24 In a multicenter study evaluating 147 consecutive pediatric patient undergoing 3CO Lenke et al reported significant improvements in the SRS-30 Self-Image, function, mental health, and satisfaction domains at a 1-year follow-up. 25 Hamilton et al prospectively studied 248 patients across 11 centers undergoing ASD sugary and demonstrated greater improvement in final ODI, SF-36 component scores, SRS-Total, and Visual Analogue Scale back scores (P < 0.05).…”
Section: Discussionmentioning
confidence: 99%
“…Alternatively, the number of patients lost to follow-up may represent a skewed sample of patients happier with their care. 32 …”
Section: Discussionmentioning
confidence: 99%
“…ASD is highly prevalent in individuals over 65 years, affecting almost 68% of that population 1 . Previous studies demonstrated that ASD patients underwent scoliosis surgery reported statistically significant improvements in all health related quality of life (HRQOL) compared with those received non‐operative treatment 2 , 3 , 4 . Generally, scoliosis surgery relies strongly on pedicle screw internal instrumentations, which can provide remarkable correction force and achieve a significant fusion rate.…”
Section: Introductionmentioning
confidence: 99%